Watt-Level Output Power Operation From Diode-Laser Pumped Circular Buried Depressed-Cladding Waveguides Inscribed in Nd:YAG by Direct Femtosecond-Laser Writing - Gabriela Salamu; Florin Jipa; Marian Zamfirescu; Nicolaie Pavel (IEEE Photonics Journal)
Circular buried depressed-cladding waveguides have been inscribed in Nd:YAG ceramic media by direct writing with a femtosecond-laser beam. A classical step-by-step translation of the medium method, as well as a newly developed helical-moving technique, were employed to fabricate waveguides with 100- $μm$ diameter. Laser emission has been obtained under the pump with a fiber-coupled diode laser. Continuous-wave output power of 3.1 W at 1.06 $μm$ and 1.6 W at 1.3 $μm$ were achieved from a waveguide inscribed by helical movement in a 4.5-mm-long 1.1-at.% Nd:YAG; the overall optical-to-optical efficiency with respect to the absorbed pump power was 0.31 at 1.06 $μm$ and 0.17 at 1.3 $μm$ . Q-switch operation has been realized with Cr 4+:YAG saturable absorber crystal. Using Cr 4+:YAG with initial transmission of 0.90, an average output power of 680 mW has been measured from a waveguide that was written by the classical method in a 7.7-mm-long 1.1-at.% Nd:YAG ceramic. The laser pulse energy was 19.7 $μJ$ , and the pulse peak power reached 7 kW.